2016
DOI: 10.1080/01616412.2016.1187825
|View full text |Cite
|
Sign up to set email alerts
|

Association between serum cystatin C levels and the severity or potential risk factors of acute ischemic stroke

Abstract: Our study suggests that there is a close relationship between cystatin C and acute ischemic stroke, independently of conventional risk factors. But the levels of cystatin C are not correlated with the stroke severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
5
5
0
Order By: Relevance
“…Its concentration in serum depends almost entirely on kidney function [30,31]. Studies suggest that CysC closely correlates with cardiovascular [22,28] and cerebrovascular diseases [32,33]. In the present study, the sCysC level at ICU admission was a predictor of AKI in patients with stroke, and this finding was consistent with those from studies involving patients undergoing cardiac surgery [25].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Its concentration in serum depends almost entirely on kidney function [30,31]. Studies suggest that CysC closely correlates with cardiovascular [22,28] and cerebrovascular diseases [32,33]. In the present study, the sCysC level at ICU admission was a predictor of AKI in patients with stroke, and this finding was consistent with those from studies involving patients undergoing cardiac surgery [25].…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, the sCysC level at ICU admission was a predictor of AKI in patients with stroke, and this finding was consistent with those from studies involving patients undergoing cardiac surgery [25]. Furthermore, Huang et al [32] retrospectively recruited 171 IS patients and found that elevated sCysC was significantly associated with incident IS. Another study from China [33] reported that a high sCysC level positively correlated with 3-month mortality among 365 patients with acute ICH.…”
Section: Discussionsupporting
confidence: 80%
“…In our study, no statistical significance was found in comparing cystatin c level and lipid profile. Matching with our study result, Xiao and colleagues [8] and Huang and colleagues [16] found that CysC levels were not correlated with serum total cholesterol, high-density lipoprotein, and low-density lipoprotein levels. While on the contrary, Xu and colleagues [6] observed a significant correlation with serum CysC levels and serum triglycerides and cholesterol.…”
Section: Discussionsupporting
confidence: 88%
“…So CysC is strongly and independently associated with arterial wall atherosclerosis. Going with our finding, Xiao and colleagues [8] and Huang and colleagues [16] found that serum CysC concentrations in stroke patients were not correlated with hypertension or diabetes. On the other hand, Yang and colleagues [7] observed a significant association between CysC level and hypertension and between CysC and diabetes.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation